Assessment of risk perception of patients concerning adverse drug reactions - Joaquim João José; Matos Cristiano; Mateos-Campos Ramona (Current Issues in Pharmacy and Medical Sciences, 2023)
Introduction. The use of medicines involves trade-offs between their therapeutic benefits and inherent risks. Several studies show that numerous adverse drug reactions (ADRs) could be avoided by increasing patients’ awareness of medicine’s risks. Even though drug labels enclose relevant information about risks and benefits, this information often requires patient education and overall health literacy to improve medication adherence, thereby preventing ADR frequency.